Assessing the User Satisfaction Perspectives of Information System: A Library Case Study in Indonesia - Syopiansyah Jaya Putra; A’ang Subiyakto; Irma Yunita; Muhamad Nur Gunawan; Yusuf Durachman (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
User satisfaction is one of the system use variables which is affected by the system creation variables in the information system (IS) success measurements, especially in the mandatory use of IS. This paper reports the relational variable assessments between three variables of the system creation dimension towards the user satisfaction variable in the library information system (LIS) implementation of a sampled university in Indonesia. Practically, the measurement has never been done since the early system implementation in the institution. The study focused on the status of the user satisfaction construct and what are the factors which influenced the construct. The used measurement model was adopted and adapted from the DeLone and McLean’s IS success model. A total of 185 respondents were selected in this study using multi-stage purposeful random sampling. The researchers used the partial least squares structural equation modeling (PLS-SEM) with the SmartPLS version 2.0 for analyzing the collected data. Findings of the study showed that users of the LIS were sufficiently satisfied and the proposed hypotheses were accepted. In terms of the adopted model, besides the findings theoretically proved that the user satisfaction construct has affected by the system creation constructs; the findings may also have proposed the practical recommendations to the sampled institution for the next LIS improvements in particular.